Fibrous Caps in Atherosclerosis Form by Notch-Dependent Mechanisms Common to Arterial Media Development. Issue 9 (15th July 2021) - Martos-Rodríguez, Carlos J.; Albarrán-Juárez, Julián; Morales-Cano, Daniel; Caballero, Ainoa; MacGrogan, Donal; de la Pompa, José Luis; Carramolino, Laura; Bentzon, Jacob F.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Atheromatous fibrous caps are produced by smooth muscle cells (SMCs) that are recruited to the subendothelial space. We tested whether the recruitment mechanisms are the same as in embryonic artery development, which relies prominently on Notch signaling to form the subendothelial medial SMC layers. Approach and Results: Notch elements were expressed in regions of fibrous cap in human and mouse plaques. To assess the causal role of Notch signaling in cap formation, we studied atherosclerosis in mice where the Notch pathway was inactivated in SMCs by conditional knockout of the essential effector transcription factor RBPJ (recombination signal-binding protein for immunoglobulin kappa J region). The recruitment of cap SMCs was significantly reduced without major effects on plaque size. Lineage tracing revealed the accumulation of SMC-derived plaque cells in the cap region was unaltered but that Notch-defective cells failed to re-acquire the SMC phenotype in the cap. Conversely, to analyze whether the loss of Notch signaling is required for SMC-derived cells to accumulate in atherogenesis, we studied atherosclerosis in mice with constitutive activation of Notch signaling in SMCs achieved by conditional expression of the Notch intracellular domain. Forced Notch signaling inhibited the ability of medial SMCs to contribute to plaque cells, including both cap SMCs and osteochondrogenic cells, and significantly reduced atherosclerosis development. Conclusions: Sequential loss and gain of Notch signaling is needed to build the cap SMC population. The shared mechanisms with embryonic arterial media assembly suggest that the cap forms as a neo-media that restores the connection between endothelium and subendothelial SMCs, transiently disrupted in early atherogenesis.